Co-infection with Trichodina (Ciliophora: Trichodinidae) and Aeromonas caviae synergistically changes the hematology and histopathology of Asian seabass Lates calcarifer - Sufardin Sufardin; Sriwulan Sriwulan; Hilal Anshary (Society for Indonesian Biodiversity, 2021)
Abstract. Sufardin, Sriwulan, Anshary H. 2021. Co-infection with Trichodina (Ciliophora: Trichodinidae) and Aeromonas caviae synergistically changes the hematology and histopathology of Asian seabass Lates calcarifer. Biodiversitas 22: 3371-3382. Consequential interaction contributed by parasitic and bacterial infections in fish has received little attention and impact of co-infection is mostly undescribed. This study identifies and describes notable damage arising from the co-infection of Trichodina and Aeromonas caviae infecting the seabass Lates calcarifer. A completely randomized experiment was performed with 4 infection treatments (healthy fish; fish naturally infected with Trichodina sp.; healthy fish injected with A. caviae; fish naturally infected with Trichodina sp. and injected with A. caviae) and 3 replicates. Fish were obtained from the Takalar Brackish Aquaculture Institute, South Sulawesi, Indonesia. The data were statistically tested using linear regression analysis. The results showed bacterial pathogenicity, lymphocyte percentage, and histopathological quantification were statistically different (P < 0.05). Meanwhile, the number of erythrocytes and leukocytes, the percentages of monocytes and neutrophils were not significantly different (P > 0.05) between treatments. The non-infected fish showed no cell inflammation and necrosis, very little hemorrhage (liver and gills), negligible hemorrhage and melano-macrophages (kidney). Kidneys and liver were the most damaged organs of co-infected fish, with a large number of inflammatory cells, hemorrhages, vacuoles, melano-macrophages, scar tissue, inflammation and necrosis. Infection with Trichodina sp. presented less damage than the co-infection of A. caviae and Trichodina sp. In conclusion, single infection showed a mild pathological impact, meanwhile, the co-infection of Trichodina sp and A. caviae contribute significantly to fish’s health.